Innovation in the Food Sector Through the Valorization of Food and Agro-Food By-Products - Novo de Barros, Ana; Gouvinhas, Irene (IntechOpen, 2021)
This book presents an integrated and multidisciplinary approach to quality and innovation in the food sector with particular emphasis on consumer perception of quality. Chapters cover such topics as identification of environmental variables, practices crops, and cultivars to improve nutritional and functional quality of different food matrices; increased preservation of biodiversity through the use of genetic resources; nutritional and functional characterization of food matrices; and evaluation of the main bioactive substances that give food its functional qualities.